Empreendedorismo e suas implicações na cadeia de suprimentos de uma indústria moageira de trigo - Freitas, Michele Medianeira Martins (2010)
Now the companies are faced with an economy o changes in the competitive environment, characterized by innovations derived from consumer demand, among other factors. In this context, the supply chain (CSs) is an important factor for achieving success, as is the new frontier of business, since the modern manufacturing excluded much of the excess time and cost of the production process. Thus, entrepreneurship can be seen as a motivational phenomenon with regard to the generation of new organizational policies. Contributing in an efficient and innovative, providing integration to the participants of CSs. From the foregoing, this research aims to study the implications of entrepreneurial skills geared to the integration of CSs in a wheat milling industry. This is a case study of a qualitative, exploratory and descriptive, based on the companies part of the CSs of Wheat Milling Industry. The results showed that relations between the actors of the CSs of the wheat milling industry in large part are strong and integrated. The skills of opportunity, and social commitment are investigated in more developed skills than conceptual, administrative and strategic equilibrium that had the answers relating to developed and developing skills. Soon, you realize that entrepreneurship has many implications in the supply chain, among them the entrepreneurial management is a relevant character-balancing, blending and dosing issues of integration and autonomy for the CSs. And these are fundamental to the success of a chain with innovative goals.